Modelagem de propriedades estruturais e eletrônicas para a otimização da Biodisponibilidade de n-piridilporfirinas atuando como moduladores redox - Oliveira, Rafael Farias de (2013)
Oxidative stress is a biological condition in which there is an imbalance between the release of reactive species and their reuptake by biological systems, leading to the production of peroxides and free radicals that damage different cellular components, including proteins, lipids and DNA. Porphyrins and their metal complexes can be used as mimics of the enzyme superoxide dismutase (SOD) in the modulation of oxidative stress. The in vivo efficacy of porphyrins is related, among other factors, to their bioavailability, which is strongly influenced by lipophilicity and can also be related to different structural and electronic properties of these molecules. In this context, the present work has the aim of analyzing the influence of certain molecular properties on the lipophilicity of a series of N-pyridylporphyrins, by means of theoretical calculations, intending to provide useful information for the design of new porphyrin derivatives. Initially, the logarithm of the octanol/water partition coefficient (log P) of these molecules was estimated by using different free software, as well as based on the difference of octanol/water free energy of solvation, employing the Density Functional Theory (DFT), with different hybrid functionals (B3LYP, M06 and M062X). From DFT calculations, electronic and structural properties were also obtained, such as atomic partial charges, molecular orbitals, dipole moment, polarizability, surface area and molecular volume. The obtained data were compared to the available experimental measure of lipophilicity to this series of porphyrins, the chromatographic retention factor (Rf). The results show that traditional and well established methods for log P calculation, such as fragmental methods, do not provide reliable results for the studied porphyrins, unlike the calculations based on free energy of solvation, which have provided similar trends to the experimental log P of manganese porphyrins analogous to the studied ones. Furthermore, the obtained results suggests that charge distribution on the porphyrin structure may be related to the observed differences in lipophilicity and, consequently, with the passage of these molecules across the cellular membrane. It also became evident that the molecular volume is strongly related to lipophilicity, since a larger relaxation of the structures in the n-octanol phase is observed due to the lipophilic character of the long alkyl chains attached to the pyridyl group. Low correlations between Rf values and the other molecular properties calculated were obtained, indicating that the lipophilicity of porphyrins can only be modulated by the size of alkyl changes and the introduction of groups that favorably alter the charge distribution.